The Relationship Between Job Demand And Workplace Well Being For Generation Z Employees In Jakarta: Hubungan Antara Job Demand Dengan Workplace Well Being Pada Karyawan Generasi Z Di Jakarta - Dominica, Vania Shafira; Wijono, Sutarto (Universitas Muhammadiyah Sidoarjo, 2019)
This study was conducted to determine the relationship between job demand and workplace well-being in Generation Z employees with a total of 120 employees aged 21-24 years who were working in an agency or company in Jakarta, using quantitative research methods with quota sampling techniques and techniques Analysis of the data used is the product moment correlation analysis. The measurement of workplace well-being variables using the workplace well-being index (Page, 2005) and job demand measurement is constructed from aspects of the job demand owned (Bakker, 2007). The results of this study indicate that there is a significant negative relationship between the variable job demand and workplace well-being with the results of the correlation coefficient r = -0.403 p <0.05.